Root Dimensions in Patients with Mild Hypodontia and a Control Group - Khalaf, Khaled; Seraj, Zahra; Hussein, Hesham; Mando, Mahmoud (European Journal of Dentistry, 2019)
Objectives The aim of this study was to compare root dimensions (length and mesiodistal widths) between subjects with mild hypodontia and an age- and sex-matched control group.Materials and Methods Root dimension measurements of all permanent teeth excluding third molars were made on standardly taken orthopantomograms of 50 individuals (25 hypodontia and 25 controls) attending the University of Sharjah Dental Hospital. The length and two mesiodistal widths were measured for each fully formed root. The length of the root was measured digitally by drawing a line from the midpoint and bisecting the mesiodistal cemento-enamel junction (CEJ) of the tooth and extended to its apex. The mesiodistal widths of each root were measured at the cervical region and at half way of and perpendicular to the length of the root.Statistical Analysis Two sample t-tests were used to compare root dimension measurements between the hypodontia and control groups.Results There were no significant differences between genders with regard to root length or widths measurements, and therefore genders were combined for further analysis. Patients with hypodontia have significantly shorter root lengths than controls for the upper central incisors, upper canines, first premolars, and lower first molars (p < 0.05). Similarly, root width at the midpoint of the root was found to be less in hypodontia group than that in controls for the upper central incisors, lower first premolars, upper first molars, and all second premolars (p < 0.05). Similar pattern of differences was found with regard to the root width at the cervical region (p < 0.05).Conclusions Patients with hypodontia have shorter and narrower roots of the whole permanent dentition except the upper lateral incisors, lower incisors, lower canines, and all second molars when compared with controls. In effect, this may affect the orthodontic treatment planning and implant placement.
Keywords: hypodontia; mild; root; dimension; control